Perbandingan Algoritma Simulated Annealing dan Harmony Search dalam Penerapan Picking Order Sequence - Tanti Octavia; Septiananda Angelica (Institute of Research and Community Outreach - Petra Christian University, 2017)
Implementation of mobile rack warehouse is commonly used in manufacturing industry because it can minimize the warehouse area used. Applying picking orders in taking of Stock Keeping Unit (SKU) on mobile rack warehouses could give fast loading order. This research aims to find out which algorithm is better in applying picking order sequence in mobile rack warehouse. The algorithm used is Simualted Annealing (SA) and Harmony Search (HS) algorithm. Both of these algorithms will be compared in terms of the gap with the shortest path method.The result shows that the HS algorithm produces a better solution than the SA algorithm with lower CPU time, but the convergence rate of HS is lower than that of SA.HS was able to produce a better solution than the shortest path method of 9 cases, while SA only 8 cases from 15 cases.